“We Can’t Compete on Human Rights”: Creating Market-Protected Spaces to Institutionalize the Emerging Logic of Responsible Management - Schuessler, Elke S.; Lohmeyer, Nora; Ashwin, Sarah (Academy of Management Journal, 2023)
To what extent are multinational corporations (MNCs) able to address grand social challenges through corporate social responsibility (CSR) in the context of a dominant market logic? Based on an in-depth qualitative study of how apparel MNCs have addressed labor standards violations since the deadly 2013 Rana Plaza factory collapse, we show how CSR managers navigate the tension between the emerging responsible management logic and the highly institutionalized market logic, revealing how some go beyond accommodating responsible management within the market by prioritizing responsible management in market-protected spaces. We theorize the construction of market-protected spaces as a multilevel mechanism for institutionalizing an emerging logic in the context of a field dominated by the market logic via three forms of institutional work: restraining the jurisdiction of the market logic, infusing the responsible management logic with nonmarket elements, and maintaining market-protected spaces against resistance. A market-protected space is an institutionally bound space that suspends the dominance of the market logic on selected issues based on a binding regulatory infrastructure that allows prioritizing responsible management practices, unlike voluntary CSR. The concept of a market-protected space maps a path for policy makers, managers, and other actors interested in institutionalizing responsible management in the global economy.